Characterization of new flavan-3-ol derivatives in fermented cocoa beans. (1st September 2018) - Fayeulle, Noémie; Vallverdu-Queralt, Anna; Meudec, Emmanuelle; Hue, Clotilde; Boulanger, Renaud; Cheynier, Véronique; Sommerer, Nicolas
Highlights: MS analysis of fermented cocoa beans showed series of signals at m / z 605 and m / z 893. Signals at m / z 605 were confirmed to be isomers of ethyl-bridged epicatechin dimers. The first identification of epicatechin-ethyl-procyanidin B2 ( m / z 893) was provided. All were formed in cocoa by condensation of epicatechin, B2, and acetaldehyde. Abstract: Two series of compounds showing mass signals at m / z 605 and 893 (negative ionization mode) have been detected in fermented cocoa beans. This study objective is to identify these mass signals and characterize their structure in fermented cocoa samples. Our hypothesis is that these signals may correspond to ethyl-bridged flavan-3-ols resulting from flavan-3-ol condensation with acetaldehyde which is a microbial metabolite. Mass spectrometry was used to compare the retention times and mass fragmentation patterns between a model solution using epicatechin and procyanidin dimer B2, the major flavan-3-ols of cocoa, as precursors and extracts of fermented cocoa. Their identification was confirmed: four isomers of ethyl-linked epicatechin as well as several isomers of epicatechin-ethyl-procyanidin B2, in which B2 was mostly linked through its upper unit, were characterized in cocoa. This study demonstrates the presence of flavan-3-ol acetaldehyde condensation products in fermented cocoa beans and provides the first report of epicatechin-ethyl-procyanidin B2.